Avaliação institucional da extensão universitária na UFPB: a regulação e a emancipação. - Serrano, Rossana Maria Souto Maior (2012)
The main question of this thesis focuses on how to process the institutional evaluation in the policy mix of higher education, particularly at the Universidade Federal da Paraíba (UFPB) and university extension. From the context of state reform and conceptions of evaluation, we seek to understand the meanings and formulations built by the institutional actors in face of evaluation practices in UFPB in the period of 1993 to 2009; to identify the dynamics of the regulatory state intervention, in which the institutional evaluation becomes the main instrument of intervention in higher education institutions. With basis on institutional documents the analysis focuses on the tension between regulation and emancipation, present in the process of applying the institutional evaluation model and at university extension from the theoretical framework of Boaventura de Sousa Santos, which in the relationship between regulation and emancipation seeks the establishment of a new common sense. From the analysis of institutional documents related to interviews with university administrators in the period screen, it is possible to infer that the relationship between evaluation and extension is tensioned in reason of a strong meritocratic and productivist component on the institutional evaluation implemented by the Brazilian government and the university extension is intended to constitute an emancipatory and transformative educational practice at the university. Accordingly, the dialogue between evaluation and extension becomes strained according to nature, interests, values and meanings.